Endocrine correlates of puberty in female Asian elephants (Elephas maximus) at the Pinnawala elephant orphanage, Sri Lanka. Issue 1 (December 2017) - Mendis, Samanthi; Jayasekera, Niromi; Rajapakse, Rajapakshalage; Brown, Janine
Abstract Background Previous studies have established ovarian cycle characteristics of adult Asian elephants using progestagen analyses, but little work has been done on young elephants to determine age at puberty. Demographic studies of wild Asian elephants suggest females give birth at about 12–18 years of age (conceiving at 10–16 years of age based on a 2-year gestation). However, there are a few examples of zoo elephants giving birth at only 5–6 years of age, so they would have started cycling much earlier. This study was carried out at the Pinnawela Elephant Orphanage (PEO) in Sri Lanka, where a herd of >80 captive elephants breeds successfully, resulting in a unique opportunity to monitor hormones and document initiation of ovarian cyclicity in young females, thus contributing to the normative reproductive database for this species. Results We measured serum progestagens in samples collected every 10 days for 18 – 24 months from 11 females (3.5–15 years of age), and found six (5.5 – 12 years of age) already were cycling at study onset. Four females started cycling during the study at 4.5, 5.5, 7.5 and 15 years of age. There were no quantitative or qualitative differences between the first pubertal luteal phase and those of subsequent cycles. Of the 46 ovarian cycles observed, 78% were associated with clear behavioral signs of estrus (heightened bull attentiveness, and willingness of females to be mounted) during the late non-luteal period when progestagens were low. The average body weight at puberty was ~48% of that of adult female elephants at PEO. Conclusions Asian elephants under human care, including under semi-captive conditions, may reach puberty earlier than those in the wild, perhaps due to better nutrition and reaching a body weight capable of supporting reproductive activity at a younger age. Thus, facilities with bulls need to carefully manage elephants to avoid accidental pregnancies in young females that may be too small to safely carry a pregnancy to term.